Nephroureterectomy for Pediatric Giant Wilms Tumor - Marwanto, Pigur Agus; Ibrahim, Ibnu Sina (Health and Medical Journal, 2025)
Introduction: Wilms' tumor most often occurs in children, with an average age of about 3 to 4 years. About 75% of cases occur in young children aged less than 5 years. These tumors usually develop in one kidney. In the United States, surgery is the first treatment for most Wilms tumors, followed by chemotherapy. According to the International Society of Pediatric Oncology, neoadjuvant chemotherapy is performed first, followed by surgery. Case Presentation: Two Years and six months child was referred to our hospital with giant abdominal mass with difficulty to determine its origin due to its large size. On examination, it was found that the abdomen was distended with a mass palpable in all of quadrant of abdomen. A contrast enhanced abdominal CT showed a solid lumpy mass in the left kidney with a size of 22.36 x 19.66 x 17.12 cm. The renal mass crossed the midline and filled most of the abdominal cavity. The contra lateral kidney shows normal function. Discussion: The most patient come with presenting complaint was abdominal mass (50%), and 35% of the patients presented with an abdominal lump. Western studies reported 74% of patients presenting with an abdominal mass. A study by Guruprasad et al reported that 90% of their patients presented with abdominal mass. Conclusion: Combination of Neoadjuvant chemotherapy and Surgery is important in the management of Wilms Tumor. Radical Nephrectomy and Ureterectomy can be performed safely if performed by an experienced surgeon